Auto-intestine transplantation for pancreatic tumors with mesenteric root involvement: a systematic review and survival-based analysis - Yadav, Dipesh Kumar; Huang, Xing; Zhang, Qi; Zhang, Gang; Bai, Xueli; Liang, Tingbo (Journal of pancreatology (Online), 2021)
To analyze a long-term survival outcome of an auto-intestine transplantation (aINTx) for the patients with locally advanced pancreatic tumor and identify the potential prognostic factors, databases were carefully searched for the studies reporting the patients with a locally advanced pancreatic tumor which typically underwent aINTx. We performed a database search using PubMed, the Cochrane Library, EMBASE, and MEDLINE to identify multiple case series of the patients who had pancreatic tumors with mesenteric root involvement and underwent aINTx, to evaluate the treatment outcomes, and calculated the patient survival using the Kaplan–Meier method and Cox proportional hazard regression analysis to properly identify an independent predictor of the survival. A total of 9 retrospective studies with a total of 29 patients were included in our study. The calculated 1-, 2-, and 3-year survival rates for the patients with pancreatic cancer and benign or low grade pancreatic tumors were 49.64%, 22.06%, and 0% versus 100%, 100%, and 80%, respectively. The corresponding median survival time was 13.4 months and 84 months, respectively. Moreover, when stratifying the pancreatic cancer patients undergoing aINTx on the basis of neoadjuvant chemotherapy (aINTx + neoadjuvant vs aINTx - neoadjuvant) there was a significant difference in the survival (P = .01). The 1- and 2-year survival rates were 75% and 75% versus 34.1% and 0%, respectively. Corresponding median survival times were 24 months and 10 months, respectively. Our analysis shows the long-term survival benefit with acceptable morbidity and mortality of pancreatoduodenectomy and aINTx for the pancreatic tumors with the mesenteric root involvement that are otherwise unresectable by the conventional surgical techniques. However, from an oncological point of view, a larger study with the control group is required to determine its safety compared to less aggressive surgical treatment.